Awareness, Perception, and Attitudes of Medical Professionals Toward Complementary and Alternative Medicine Devices in Rheumatism: A Survey of Tripoli Community Pharmacies (Razi Medical Journal, 2025)
Recently, a patient-led revolution has occurred in Complementary and Alternative Medicine (CAM). In terms of incidence and prevalence, Rheumatic Diseases cover a wide range of illnesses. There is still uncertainty regarding the therapeutic benefits of CAM-Copper Bracelets and other magnetic devices for Rheumatoid arthritis (RA) patients, which have not been thoroughly investigated. However, the medical professionals' (MP) beliefs in CAM (awareness, perception of use, and attitude) are also not yet well reviewed, and there is little communication or accountability among MPs. This study aimed to gain a thorough comprehension of beliefs possessed by (MP) CAM-Copper Bracelets in the context of Tripoli-Libya, Ain Zara Community Pharmacies (ComPh.); this cross-sectional study surveyed (n=72) MPs in local (ComPh.). A total of 56 participants provided the completed responses. The overall response rate was 77% using a validated self-constructed questionnaire based on the Likert Scale.  Data analysis included Median, Mode score, Pearson chi-square tests, and frequency percentage distributions across various questionnaire statements. The data shows a young, predominantly male workforce with a balanced range of experience levels. Pharmacists 28 (50%) and physicians 24 (42.9%) are the primary job titles. Experience levels were evenly distributed, 19 (33.9%), with a Median of 2 years and a Mode of 2. All in all, 34 (60.7%) cited informal sources of CAM information, the highest experience 4yrs+ group was most skeptical (50%), p=0.031.    Pharmacists 56% and Physicians 44% show a stronger tendency to be skeptical or express a lack of confidence in the efficacy of CAM-Copper bracelets, p=0.003; the Medical Assistance (MS) staff are less likely to express a negative 2 (9%), p=0.003 or neutral opinion 2 (13%), p=0.001. Survey data revealed a significant deviation in professional perspectives: a substantial proportion of pharmacists believe certain complementary and alternative medicine (CAM) therapies are likely effective (p = 0.003), whereas physicians demonstrated notable uncertainty, particularly regarding CAM's efficacy for arthritis symptoms and joint mobility. Nevertheless, the results of Magnetic WS and Metallic Devices showed no statistically significant relationship.
Keywords: CAM, Copper Bracelets, Rheumatism, Awareness, Perception, Attitude.